Seeds in Chernobyl: the database on proteome response on radioactive environment - Klubicová, Katarína; Vesel, Martin; Rashydov, Namik; Hajduch, Martin (Frontiers in Plant Science, 2012)
Two serious nuclear accidents during the last quarter century (Chernobyl, 1986 and Fukushima, 2011) contaminated large agricultural areas with radioactivity. The database “Seeds in Chernobyl” (http://www.chernobylproteomics.sav.sk) contains the information about the abundances of hundreds of proteins from on-going investigation of mature and developing seed harvested from plants grown in radioactive Chernobyl area. This database provides a useful source of information concerning the response of the seed proteome to permanently increased level of ionizing radiation in a user-friendly format.